Ethnomusicology, Queerness, Masculinity Silence=Death - Amico, Stephen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
This open access book explores the disciplinary and recent interdisciplinary sites, relations, and productions of ethnomusicology and queerness, arguing that both are founded upon a destructive masculinity$1 (Bindissolubly linked to coloniality and epistemic hegemony$1 (Band marked by a monologic, ethnocentric silencing of embodied, same-sex desire. Ethnomusicology$1 (Bs fetishization of masculinizing fieldwork; queerness$1 (Bs functioning as Anglocentric master category; and both spheres$1 (Bdevaluation of sensuality and experience, concomitant with an adherence to provincial, Western conceptions of knowledge production, are seen as precluding the possibility of an equitable, dialogic pluriversality. Ultimately reimagining the fates of both in relation to negative emotions and intractable affect, and enlisting the sonic as theoretical-material intervention, the disciplines are envisioned as vanquished, replaced by explorations of sound, sex/uality, and experiential somaticity occurring in a protean, postdisciplinary space of material/epistemic equity. This uncompromising and long-overdue critique will be of interest to researchers and students from numerous disciplinary and theoretical backgrounds, including music, sound, gender, queer, and postcolonial/decolonial studies. Stephen Amico is Associate Professor of Musicology at the University of Bergen, Norway. He is the author of Roll Over, Tchaikovsky!: Russian Popular Music and Post-Soviet Homosexuality (2014).s
1. Introduction: Silencing -- 2. 'This is to Enrage You' -- 3. We Don't Need Another Hero -- 4. Street Cred and Locker Room Glances -- 5. Diverse People in Special Places -- 6. (No) Body/ (No) Homo -- 7. Affecting the Colonist -- 8. Non-fundamental Tones; or, The Pharmakon of Silence -- 9. Conclusion: 'Such People Do Not Exist'.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Music; Queer theory; Philosophy; Postcolonialism; Race; Music; Queer Studies; Postcolonial Philosophy; Race and Ethnicity Studies